Brotar: design de serviço para um consumo consciente de alimentos in natura - Machado, Paloma Sangali (My University, 2025)
The monograph I present to you is the result of the research carried out for the Completion of the Bachelor's Degree in Design, along with the brand, service and product, which will contribute to complete the project, which addresses the subject of conscious eating and the incentive for a change in habit, with new experiences like knowing, cultivating and preparing. Addressing the subject of food is also learning to undo old beliefs, it is being able to draw a profile of people who seek to rethink their lives and be connected with the whole. Technology has brought many changes to people's lives, and this has also impacted food. It is possible to find pesticides, antibiotics, modified seeds, among other things, in many products that are present on supermarket shelves. It is necessary to review our habits, seek information about food, and also understand how its life cycle is through cultivation. But this feeling needs to come from within people, those who are endowed with the power of decision. During the entire research process, it was possible to find points that would be necessary to go deeper, subjects such as where the food comes from, what are its benefits, what it is like to have a fast and slow life, tracing this path, it was possible to prepare interviews that contributed to validate previously collected ideas. As a design solution, a digital platform was developed that contributes to grouping a large amount of coherent information about food, with this, in addition, a cultivation manual was also created, which will help to encourage the search for knowledge. The illustrations will be the key part of the work, as they help to complement and make the subjects more fun, but without losing their importance and credibility, so it will be possible to find them in all projects. In addition to information, it is possible to interact with the entire food phase, planting, therefore, as a solution for the product project, self-irrigation vases were thought, which will bring this independence to those who choose to participate in this moment. The visual identity and its points of contact, along with the product and service, are aligned with the brand's proposal and concept. [resumo fornecido pelo autor]
A monografia que vos apresento é o resultado da pesquisa realizada para a Conclusão do Curso de Bacharelado em Design, juntamente a marca, serviço e produto, que contribuirá para completar o projeto, que aborda o assunto sobre alimentação consciente e o incentivo para uma mudança de hábito, com novas experiências como conhecer, cultivar e preparar. Abordar o assunto sobre alimentação é também aprender a desfazer velhas crenças, é conseguir traçar um perfil de pessoas que buscam repensar a sua vida e estar conectado com o todo. A tecnologia trouxe muitas mudanças na vida das pessoas, e isso impactou também nos alimentos. É possível encontrar agrotóxicos, antibióticos, sementes modificadas, entre outras coisas, em muitos produtos que se fazem presente nas prateleiras dos supermercados. É necessário rever nossos hábitos, buscar informações sobre os alimentos, e também entender como é o seu ciclo de vida, através do cultivo. Mas esse sentimento precisa vir de dentro das pessoas, essas que são dotadas do poder da decisão. Durante todo o processo de pesquisa, foi possível encontrar pontos ao qual seria necessário aprofundar mais, assuntos como de onde vem o alimento, quais são seus benefícios, como é ter uma vida fast e slow, traçando esse caminho, foi possível elaborar entrevistas que contribuíram para validar as ideias coletadas anteriormente. Como solução projetual, desenvolveu-se uma plataforma digital que contribui para agrupar uma grande quantidade de informações coerentes sobre os alimentos, com isso, para complementar, criou-se também um manual de cultivo, que contribuirá para incentivar a busca do conhecimento. As ilustrações serão a peça chave do trabalho, pois ajudam a complementar e deixar os assuntos mais divertidos, mas sem perder a sua importância e credibilidade, por isso, será possível encontrá-las em todos os projetos. Além da informação, é possível interagir com toda a fase do alimento, plantando, por isso, como solução do projeto de produto, pensou-se em vasos autoirrigáveis, que trarão essa independência para aqueles que optarem em participar desse momento. A identidade visual e seus pontos de contato, juntamente com o produto e o serviço, se alinham à proposta e conceito da marca. [resumo fornecido pelo autor]
Keywords: Alimentos naturais; Design